Analysis of Meat Mineral Content in Cemani Chicken with Homozygous (Fm/Fm) and Heterozygous (Fm/fm+) Genotypes - Rona Saumy Safitry; A B Dharmayanthi; K Kinoshita; T Akiyama; S Darwati; Tatan Kostaman; S Sopiyana; I Khaerunnisa; Cece Sumantri (Jurnal Ilmu Ternak dan Veteriner, 2022)
Cemani chicken is an Indonesian native chicken with black hyperpigmentation on feathers, skin, beak, comb, and flesh. Hyperpigmentation in chickens is called Fibromelanosis. Fibromelanosis in Cemani chickens is semi–dominant, producing two genotypes: homozygous (Fm/Fm) and heterozygous (Fm/fm+). Cemani chicken meat’s black color may indicate a higher mineral content than regular chicken meat. The study’s is aims are to detect genotype homozygous (Fm/Fm) and heterozygous (Fm/fm+) mutations and to determine the mineral content of Cemani chickens with homozygous (Fm/Fm) and heterozygous (Fm/fm+) genotypes. In the Cemani chicken population (n = 32), the Fm–specific allele genotype was detected using a Polymerase Chain Reaction–Restriction Fragment Length Polymorphism (PCR–RFLP) and the MluI restriction enzyme. The mineral contents of Cemani chicken tested were Fe, Zn, Mn, and Se. The results showed that homozygous Cemani chickens (Fm/Fm) had higher Fe and Zn mineral content. However, the homozygous (Fm/Fm) and heterozygous (Fm/fm+) Cemani chicken were not different in mineral content of Se and Mn. This study found that different genotypes of Cemani chicken had different mineral compositions. In the future, this analysis supports the selection of chicken strains with high antioxidant levels.